Population development as a driver of coastal risk: Current trends and future pathways. (31st January 2023) - Reimann, Lena; Vafeidis, Athanasios T.; Honsel, Lars E.
Abstract: Abstract: Coastal areas are subject to hazards that can result in severe impacts due to the high concentration of people and assets in exposed locations. While climate-induced sea-level rise will exacerbate these hazards in the course of the 21st century, future dynamics in socioeconomic development will play an important role in driving impacts – as well as adaptation responses – in particular in countries with rapid population growth in low-lying coastal areas. Here, we synthesize the current state of knowledge related to current and future population development in coastal locations and the underlying trends in socioeconomic development affecting coastal impacts at continental to global scales. Currently, 2.15 billion people live in the near-coastal zone and 898 million in the low-elevation coastal zone globally. These numbers could increase to 2.9 billion and 1.2 billion, respectively, depending on the socioeconomic scenario (i.e., Shared Socioeconomic Pathway [SSP]) considered. Nevertheless, although these numbers indicate a rapid increase in exposure of population and assets to coastal hazards, they bear limited information about the actual impacts as they do not include information on the vulnerability of coastal population. Based on these insights, we stress the need to account for dynamics in socioeconomic development in coastal risk assessments, including exposure as well as vulnerability, and additionally exploring potential feedbacks due to adaptation responses and migration decisions. Last, we propose action points for future work that can inform long-term coastal planning for managing coastal risks.